Maastrichtian (Late Cretaceous) ammonites from the Owl Creek Formation in northeastern Mississippi, U.S.A - Kennedy, W; Cobban, W (2000)
Ammonites are locally abundant in the Owl Creek Formation in northeastern Mississippi. The assemblage is dominated numerically by Eubaculites carinatus (MORTON, 1834), a widely distributed marker fossil for the Maastrichtian that also occurs in South America, southern Africa, Madagascar, western Australia, southern India, and western Europe. It is accompanied by Sphenodiscus pleurisepta (CONRAD, 1857). Baculites cf. B. claviformis STEPHENSON, 1941, B. cf. B. undatus STEPHENSON, 1941, Discoscaphites iris (CONRAD, 1858), D. sphaeroidalis sp. nov., and D. cf. D. conradi (MORTON, 1834).